Penguatan Kapasitas Masyarakat dalam Pengelolaan Sampah Berkelanjutan di Kampung Ekowisata Keranggan: Strengthening Community Capacity for Sustainable Waste Management in Kampung Ekowisata Keranggan - Novita Uki Hutami; Khairun Nisa; Rizky Rivaldi Afghani; Katerina Susrianti; Rini Subekti; Ginta Ginting (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Waste management in Kampung Ekowisata Keranggan, South Tangerang, faces challenges due to limited facilities and low community awareness and commitment in sorting and processing household waste effectively. These issues threaten the quality and the conservation of the ecotourism environment. Based on these issues, a community service program was implemented using a zero-waste approach focused on building human resource capacity. This program utilized community-based waste management, including observation and a preliminary survey, a focus group discussion, and a workshop. The results showed significant improvements in community knowledge, skills, and environmental awareness, as well as support from local leaders (local champion), which fostered sustainable waste management practices. These findings help enhance the quality of household waste management and strengthen environmental conservation in the ecotourism area.